Combination of percutaneous left appendage epicardial ligation and endo-epicardial atrial fibrillation ablation - Grossi, Stefano; Bianchi, Francesca; Blandino, Alessandro; Pintor, Chiara; Tomasello, Antonino; Mabritto, Barbara; Musumeci, Giuseppe (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is the main cause of cardioembolic stroke. In high bleeding risk patients, long-life anticoagulation therapy is not permitted and left atrial appendage (LAA) closure may be considered. LAA is also a critical substrate for AF. Epicardial LAA occlusion has several advantages: LAA ligation results in a favourable electrical and structural atrial remodelling, which decreases AF recurrence. Endocardial ablation alone is not efficient for all patients and new evidence shows better outcomes in patients affected by persistent AF after a combined hybrid endo/epicardial ablation. Considering the synergic potential of these techniques, in this case series they were both combined in a single procedure.We describe the treatment of 5 patients referred for refractory AF ablation and LAA closure. All patients had high thrombotic and previous major haemorrhage with relative contraindication to lifelong therapy with anticoagulation. Combine procedure of LAA ligation and endo-epicardial ablation was scheduled with short-term anticoagulation.LAA closure was performed, with an epicardial approach using the LARIAT system, then LA mapping and ablation was performed, endocardially and then epicardially.All procedures were concluded without complications.At follow-up in all patient's transoesophageal echocardiography showed the complete occlusion of the LAA, therefore anticoagulation therapy was interrupted; all patients were asymptomatic and in sinus rhythm, no haemorrhage nor ischemic events occurred.Combination of percutaneous LAA ligation and endo-epicardial ablation revealed to be feasible and safe and might represent a new approach for the treatment of refractory AF in patients with indication for LAA occlusion.